Studi Kasus Perancangan Rangka Motor Listrik Tipe Naked Bike Menggunakan ANSYS - Putra, Arya Pratama; Basuki, Budi; Sugiyanto; Wibowo, Setyawan Bekti (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
The function of the frame on the electric motorcycle is to support the rider's load and where several motor components are combined, and also acts as the basic form of the motorcycle itself. The design of the electric motorcycle frame design also needs a finite element analysis. The analysis computes and produces formulas to estimate the actions that can be performed on the object, where this method involves dividing the structure into smaller elements connected by nodes or in other words, the discretization of elements. The objective of this research is to analyze the yield strength level of the electric motorcycle frame design under static loading conditions in accordance with the load safety standards of two-wheeled vehicles in Indonesia. The subject of this research is an electric motorcycle frame design with a naked bike frame type. The material used in the frame is aluminum alloy 6061 T6. The total loading during simulation is 265 kg. The quality of element discretization obtained in the electric motorcycle frame design is 0,278 with the size of each element of 5,5 mm. The maximum von Misses stress obtained is 125,3 MPa with a maximum deformation of 0,08618 mm and the safety factor is 2,154. The results of this study provide a statement that the electric motor frame design is able to withstand the load during simulation.